(untitled) (Universitas Medica, 2024)
Introduction: Helicobacter pylori infection has been associated with various gastrointestinal disorders, including chronic gastritis, peptic ulcers, dyspepsia, and gastric cancer. This study aimed to compare the effectiveness of four invasive diagnostic methods for detecting H. pylori in 297 patients with premalignant gastric lesions and gastric cancer. Method: In this cross-sectional study, the methods evaluated included Giemsa stain (GST), culture, rapid urease test (RUT), and polymerase chain reaction (PCR). Patients were recruited between 2016 and 2019 in Ibagué – Colombia, and a Case Definition Criteria (CDC) was used for diagnosis. Analysis of operational and epidemiological characteristics was performed to assess result agreement. Results: According to this, it showed that H. pylori infection rates of 43% (RUT), 63% (GST), 24% (culture), and 42% (PCR). The Kappa index demonstrated higher values for PCR (0.7704) and RUT (0.7030) compared to other methods. The RUT test displayed the highest Kappa index (0.59) when compared to PCR. Non-parametric tests indicated that PCR (0.779) and RUT (0.708) had the strongest correlation, reducing prediction error by 51.1% and 40.4%, respectively. Conclusion: The CDC criteria exhibited enhanced reliability in diagnosing H. pylori infection. Notably, PCR and RUT showed significant correlation in diagnostic accuracy for H. pylori detection.